SaeboGlove therapy for upper limb disability and severe hand impairment after stroke (SUSHI): Study protocol for a randomised controlled trial. (September 2021) - Alexander, Jen; Langhorne, Peter; Kidd, Lisa; Wu, Olivia; McConnachie, Alex; van Wijck, Frederike; Dawson, Jesse
Background: Impaired active digital extension is common after stroke, hindering functional rehabilitation, and predicting poor recovery. The SaeboGlove assists digital extension and may improve outcome after stroke. We recently performed a single group, open, pilot trial of the SaeboGlove early after stroke which demonstrated satisfactory safety, feasibility and acceptability. An adequately powered randomised clinical trial is now needed to assess the clinical effectiveness of the SaeboGlove. Methods: SUSHI is a pragmatic, multicentre, parallel-group, randomised controlled trial with blinded outcome assessment, and embedded process and economic evaluations. Adults, 7–60 days post-stroke, with upper limb disability and severe hand impairment, including reduced active digital extension, will be recruited from NHS inpatient stroke services in Scotland. Participants will be randomised on a 1:1 basis to receive 6 weeks of self-directed, repetitive, functional-based practice involving a SaeboGlove plus usual care, or usual care only. The primary outcome is upper limb function measured by the Action Research Arm Test (ARAT) at 6 weeks. Secondary outcomes will be measured at 6 and 14 weeks. A process evaluation will be performed via interviews with 'intervention' participants, and their carers and clinical therapists. A within-trial cost-effectiveness analysis will be performed. 110 participants are required to detect a difference between groups of 9 in the ARAT with 90% power at a 5% significance level allowing for 11% attrition. Discussion: SUSHI will determine if SaeboGlove self-directed, repetitive, functional-based practice improves upper limb function after stroke, whether it is acceptable to stroke survivors and whether it is cost-effective.